Medical consequences of radiation exposure of the bronchi—what can we learn from high-dose precision radiation therapy?. (1st November 2021) - Lindberg, Karin; Onjukka, Eva
Abstract: The bronchial tolerance to high doses of radiation is not fully understood. However, in the event of a radiological accident with unintended exposure of the central airways to high doses of radiation it would be important to be able to anticipate the clinical consequences given the magnitude of the absorbed dose to different parts of the bronchial tree. Stereotactic body radiation therapy (SBRT) is a radiation treatment technique involving a few large fractions of photon external-beam radiation delivered to a well-defined target in the body. Despite generally favourable results, with high local tumour control and low-toxicity profile, its utility for tumours located close to central thoracic structures has been questioned, considering reports of severe toxic symptoms such as haemoptysis (bleedings from the airways), bronchial necrosis, bronchial stenosis, fistulas and pneumonitis. In conjunction with patient- and tumour-related risk factors, recent studies have analysed the absorbed radiation dose to different thoracic structures of normal tissue to better understand their tolerance to these high doses per fraction. Although the specific mechanisms behind the toxicity are still partly unknown, dose to the proximal bronchial tree has been shown to correlate with high-grade radiation side effects. Still, there is no clear consensus on the tolerance dose of the different bronchial structures. Recent data indicate that a too high dose to a main bronchus may result in more severe clinical side effects as compared to a smaller sized bronchus. This review analyses the current knowledge on the clinical consequences of bronchial exposure to high dose hypofractionated radiation delivered with the SBRT technique, and the tolerance doses of the bronchi. It presents the current literature regarding types of high-grade clinical side effects, data on dose response and comments on other risk factors for high-grade toxic effects.